Harmonization on messaging of RCMAS Climate+ and ACAP - Balanza, Jane Girly; Castillo, Rowena (International Rice Research Institute, 2024)
This report presents the results of a 1 day workshop participated by 10 staff from 4 organizations. The workshop aimed to harmonize the crop management recommendations for rice of the Rice Crop Manager and Advisory Service (RCMAS) and Agro-climatic Advisory Portal for consistent messaging. During the workshop, relevant crop management practices that are critical in the different growth stages of rice were discussed. This guided the development and enhancement of the generic crop and nutrient recommendation from ACAP.